2018
DOI: 10.4172/2472-0992.1000148
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Studies of the Ethyl Acetate Extract of the Fruit of Piper capense

Abstract: Natural products have been a major source of drugs for centuries. The fruit of Piper capense is used traditionally as spice and for the treatment of infectious diseases in different parts of Ethiopia. The main objective of this work is to carry out phytochemical study of the EtOAc crude extract of the fruit of P. capense. Phytochemical screening on this crude extract revealed the presence of phenols, alkaloids, steroids, terpenes, saponins and flavonoids. After silica gel column chromatography the crude extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Figure demonstrates 1 H– 1 H COSY, HMQC, and HMBC correlations in compound 2 . The spectral data for compound 2 is in well agreement with 5 - hydroxy-7,4′-dimethoxyflavone reported in ref .…”
Section: Results and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Figure demonstrates 1 H– 1 H COSY, HMQC, and HMBC correlations in compound 2 . The spectral data for compound 2 is in well agreement with 5 - hydroxy-7,4′-dimethoxyflavone reported in ref .…”
Section: Results and Discussionsupporting
confidence: 89%
“…An absorption band appeared at 285 nm on the UV spectrum. 3, which are similar to aquilarinenside E previously isolated from Aquilaria sinensis leaves 34 and flower buds, 45 compound 6 is identified as aquilarinenside E. 40 The HRESIMS spectrum of compound 7 revealed a significant peak at m/z 391.1002 [M − H] − indicated to the molecular formula of C 19 H 20 O 9 , while the UV spectrum demonstrated a maximum absorption band at 285 nm. IR spectrum revealed absorption bands at 3326, 1635, and 1595 cm −1 recognized as OH, CO, and aromatic groups absorptions, respectively.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Thus, compound 4 was identified and confirmed as 5-hydroxy-7,4′-dimethoxyflavone by comparison with reported data. 23 The MS (ESI − ), NMR spectroscopic data in DMSO-d 6 suggested that compound 5 was also a flavon derivative with two methoxy groups and two hydroxy groups. Based on HMBC data, the two methoxy groups were attached at C7 and C3′, meanwhile two hydroxy groups were linked at the C5 and C4′ positions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%